2012
DOI: 10.1007/s00005-012-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity to Biologics: Mechanisms, Prediction and Reduction

Abstract: Currently, there is a significant rise in the development and clinical use of a unique class of pharmaceuticals termed as Biopharmaceuticals or Biologics, in the management of a range of disease conditions with, remarkable therapeutic benefits. However, there is an equally growing concern regarding development of adverse effects like immunogenicity in the form of anti-drug antibodies (ADA) production and hypersensitivity. Immunogenicity to biologics represents a significant hurdle in the continuing therapy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 165 publications
0
139
1
Order By: Relevance
“…A single intravenous dose of idarucizumab, a monoclonal antibody fragment, has a low potential to stimulate ADA formation. Nevertheless, the use of a biologic agent may be a potential risk factor for immunogenicity in the form of ADA production 44. A pooled analysis of data from three phase 1 studies found that pre‐existing and treatment‐emergent antidrug antibodies were present at low levels and had no impact on the PK/PD of idarucizumab in adults 45.…”
Section: Discussionmentioning
confidence: 99%
“…A single intravenous dose of idarucizumab, a monoclonal antibody fragment, has a low potential to stimulate ADA formation. Nevertheless, the use of a biologic agent may be a potential risk factor for immunogenicity in the form of ADA production 44. A pooled analysis of data from three phase 1 studies found that pre‐existing and treatment‐emergent antidrug antibodies were present at low levels and had no impact on the PK/PD of idarucizumab in adults 45.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, determination of epitope specificity is recommended for nonendogenous fusion molecules, such as antibody-drug conjugates. Second, for multi-regional clinical trials, the frequency of ADA formation could differ among ethnicities as some reports showed an association of highly variable human leukocyte antigen types with ADA formation [20].…”
Section: Study Sample Analysismentioning
confidence: 99%
“…63 As an alternative therapeutic strategy to TNF-a inhibitors, treatments that manipulate leukocyte adhesion, costimulatory signaling and cytokine receptors are emerging as potential treatments for IBD. The current therapeutic approach for fistulising CD, in case of uncomplicated perianal fistulae, is based on seton placement, while abscesses and other complications require surgical intervention combined with medical therapy, which usually includes anti-TNF, antibiotics and thiopurines.…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%